Large economic spaces : options for Latin America and the Caribbean - Aninat, Augusto (UN New YorkUS, 1995)
Presents an overview of the large economic spaces and the process of economic integration in the Western Hemisphere. Looks at Latin America and large economic spaces as well as the strategic options for Latin america in the context of economic integration processes.